Post-Stroke Depression and Suicidal Ideations: Relationship with Gender and Marital Status: A Cross Sectional Study - Mgbeojedo Ukamaka Gloria; Osiri Emmanuel Jonah; Akosile Christopher Olusanjo; Okoye Emmanuel Chiebuka; John Jeneviv Nene; Akobundu Uzoamaka Nwakego; Anyaene Chiamaka Chinyere (SAGE Publishing, 2024)
Objectives: To determine the prevalence and contributing factors of depression and suicidal ideations among stroke survivors in Nigeria. Methods: This was a cross-sectional study comprising 75 consenting stroke survivors who were purposively recruited from 2 tertiary hospitals. Suicidal ideations and depression were measured using standard questionnaires. Obtained data was analyzed with appropriate statistical tools. Results: 9.3% of the participants had depression while 4% reported suicidal ideations. Significant correlation existed between suicidal ideations and depression (ρ = .31, P  = .01), and levels of depression and suicidal ideations (χ 2  = 85.76; P  < .01). Depression had a significant relationship with gender and marital status, while suicidal ideations had a significant relationship with marital status. Females were significantly more depressed than their male counterparts ( U  = 512.50, P  = .04) and also had a higher score on suicidal ideations. The widowed/divorced recorded the highest scores on depression (χ 2  = 8.77, P  = .01) and suicidal ideations (χ 2  = 6.62; P  = .04). Conclusion: A worrisome prevalence of depression was reported among the study participants. The level of suicidal ideations was quite low. Depression and suicidal ideations were higher among females and those who lost their life partners (either by divorce or death).